2020
DOI: 10.1177/0142331220936584
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear control design using Takagi-Sugeno fuzzy applied to under-actuated visual servo system

Abstract: This paper presents the Takagi-Sugeno (TS) fuzzy control design for nonlinear stabilization and tracking control of a ball on plate system. To deal with the plant nonlinearity and the fuzzy convergence issue, we formulate the parallel distributed compensator (PDC) TS fuzzy model to characterize the global behaviour of the nonlinear system and synthesize a feasible control framework using a velocity compensation scheme. The nonlinear dynamics of the ball on plate system is obtained using the Euler-Lagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The nonlinear dynamical equation of the ball balancer is obtained using the Euler–Lagrangian approach. For detailed overview on modelling of two DoF ball balancer, interested readers can refer to (Jonnalagadda et al, 2020)…”
Section: Application: Ball Balancermentioning
confidence: 99%
“…The nonlinear dynamical equation of the ball balancer is obtained using the Euler–Lagrangian approach. For detailed overview on modelling of two DoF ball balancer, interested readers can refer to (Jonnalagadda et al, 2020)…”
Section: Application: Ball Balancermentioning
confidence: 99%
“…With the development of control theory, some nonlinear control methods have been applied to switched reluctance motors to improve the control performance [21,22]. Fuzzy control has certain robustness to time-varying load and is suitable for controlling nonlinear, time-varying, lagging, and incomplete model systems [23,24]. Setting fuzzy control based on artificial experience has gradually developed into a mature theory and is widely used in motor control [25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a great theoretical interest, fuzzy adaptive control usually requires online complex adaptation laws to deal with unknown parameters and nonlinearities, which may induce real-time difficulties. Since robot modeling has been well-established (Dawson et al, 2003), fuzzy model-based control approaches would be more appropriate for high-speed motion tracking of industrial manipulators as recently shown in Nguyen V-A, et al (2019) and Jonnalagadda et al (2020). Note that the existing fuzzy model-based approaches mostly rely on the well-known H specification to guarantee the tracking performance, which can lead to the following drawbacks, especially for complex industrial manipulators.…”
Section: Introductionmentioning
confidence: 99%